Properties of oil palm shell lightweight aggregate concrete containing unground palm oil fuel ash as fine aggregate replacement - Mohd Hanafi, Hashim (2020)
Environmental degradation due to increasing granite aggregate quarrying and river sand mining to supply the construction industry needs is an issue which need to be solved. At the same time, the disposal of oil palm shells (OPS) and palm oil fuel ash (POFA) from palm oil mills is causing environmental pollution. In view of sustained supply of natural aggregate and a more environmental friendly palm oil industry, the present research attempt to integrate both palm oil wastes as alternative aggregates in concrete. Thus, this research investigates the effect of unground POFA content as partial fine aggregate replacement towards mechanical and durability of OPS lightweight aggregates concrete. At the first stage, trial mix has been conducted to select the optimum lightweight concrete mix design. The effect of air and water curing regime on this environmental friendly concrete containing unground POFA ranging from 5%, 10%, 15% and 20% by weight of sand were examined in term of the compressive strength, splitting strength, flexural strength and modulus of elasticity for a duration of 1 year. Testing on durability performance of the concrete specimens in the aspect of acid resistance, sulphate resistance and carbonation has been conducted. The finding shows that water cured OPS LWAC with 10% of unground POFA as sand replacement performs the best amongst all concrete specimens. The application of optimum amount of sand replacement resulted in a better densification from the pozzolanic reaction and filler effect by unground POFA thus making the OPS LWAC denser and stronger. However, inclusion of unground POFA up to 20% produces concrete with the lowest mechanical strength values. As for curing effect, the water curing specimen shows better result in term of compressive, flexural, splitting and modulus of elasticity compare with the air curing specimen. Water cured OPS LWAC containing 10% of unground POFA achieve higher durability against acid and sulphate attack compare with the other specimen. All specimens for air and water curing present the good result in term of water absorption testing where the result is below than 10% which is represent as a good quality of concrete. No carbonation rate was detected for specimen subjected to water curing until the age of 365 days. Air cured specimens begins to carbonate at age of 180 days where specimen contain 10% amount of unground POFA have the lowest carbonation value compare with control specimen and the other percentage of replacement specimen. Water curing promotes undisturbed hydration process and pozzolanic reaction which enhances the durability of OPS LWAC specimen with 10% POFA as compared to the air cured ones. Conclusively, success in utilizing unground POFA as partial fine aggregate replacement in OPS lightweight aggregate concrete would reduce quantity of natural sand mined from the river and amount of palm oil solid waste disposed at landfill.